Absence of cytochrome P450 2A5 enhances alcohol-induced liver injury in mice. Issue 6 (June 2015) - Hong, Feng; Liu, Xiyu; Ward, Stephen S.; Xiong, Huabao; Cederbaum, Arthur I.; Lu, Yongke
Abstract Background Ethanol can induce cytochrome P450 2E1, an active generator of reactive oxygen species, and this cytochrome is considered a risk factor for oxidative liver injury. Recently, we found that in addition to P450 2E1 also cytochrome P450 2A5, another isoform of cytochrome P450, can be induced by ethanol, and that ethanol induction of cytochrome P450 2A5 is P450 2E1-dependent. Aims To investigate the role of cytochrome P450 2A5 in alcohol-induced liver injury. Methods Cytochrome P450 2A5-knockout mice and wild type mice were fed the Lieber–Decarli ethanol liquid diet to induce liver injury. Controls were fed the Lieber–Decarli control diet. Results After 4 weeks of feeding with Lieber–Decarli diet, ethanol-induced liver injury was enhanced in the knockout mice compared with wild type mice, as indicated by serum transaminases, hepatic fat accumulation (steatosis), and necroinflammation observed in liver sections with Haematoxylin & Eosin staining. Ethanol-induced oxidative stress was also higher in the knockout mice than the wild types. Ethanol feeding induced cytochrome P450 2A5 in wild type mice but not in the knockout mice, while induction of cytochrome P450 2E1 was comparable in the knockout and wild type mice. Conclusion These results suggest that cytochrome P450 2A5 protects against ethanol-induced oxidative liver injury.